Kinetic Model for Enzymatic Hydrolysis of Cellulose from Pre-Treated Rice Husks - Winta Efrinalia; Novia Novia; Elda Melwita (Fermentation, 2022)
Rice husks contain cellulose as a raw material for manufacturing second-generation bioethanol. Cellulose from pre-treated rice husks was converted into reducing sugars through enzymatic hydrolysis using enzymes derived from Aspergillus niger. This study aims to determine the kinetics of enzymatic hydrolysis at enzyme concentrations of 10, 15, and 20% (v/w) and hydrolysis times of 5, 10, 15, 20, and 25 h. The results showed that cellulose was hydrolyzed to form reducing sugars. The CMCase activity and FPase activity reached 548.940 and 314.892 U mL−1, respectively, much higher than most previous reports on this genus. From the calculation of the reaction rate using the Michaelis–Menten kinetic model, the value of the Michaelis constant ranges from 0.001 to 0.0007, and the maximum rate is 1.3 × 10−7 to 2.7 × 10−7 Mol L−1 s−1. The highest reducing sugar concentration was obtained (1.80 g L−1) at an enzyme concentration of 20% (v/w) and a hydrolysis time of 25 h.